THE PROBLEM OF THE QUALITY OF LIFE IN CHRONIC HEART FAILURE - V. N. Kovalenko; L. G. Voronkov (Евразийский Кардиологический Журнал)
Clinically manifested chronic heart failure (CHF) is associated with significant decrease of patients' qualityoflife(QL)caused by their functional capability as well as their psychoemotional discomfort. Most informative predictors of QL in CHF are its ischemic origin, age, female sex, NYHA functional class (FC), tachycardia at rest, creatinine clearance, Hb, uric acid and plasma cholesterol levels, moderate-to-severe depression. Data of Minnesota Heart Failure Life Quality/SF-36 questionnaires demonstrate high prognostic value in regard of 1 - 5 year survival in CHF patients with the same NYHA class and so may be useful in risk stratification of patients with comparable functional status.